An Analysis of Changes in the Distribution of Employment Between the Manufacturing and Service Industries 1960-1970 - Haig, B. D. (The Review of Economics and Statistics, 1975)
SINCE the formulation of the Fisher-Clark hypothesis of structural change, which associates changes in the distribution of employment between industries with changes in levels of real income per head, economists have been interested in the reasons behind changes in industry structure.' interest has received a fillip in recent years with an apparent acceleration in the rate of growth of employment in the service sector compared with that in the manufacturing sector.2 Recent empirical studies by, for example, Fuchs (1965) and Dowie (1970) have sought to explain the relatively faster rate of growth of employment in service industries than in manufacturing (or goods) industries in terms of the supply and demand characteristics of the products of the two sectors. In both studies it was found that the ratio of product of the two sectors remained fairly constant but that there was an appreciably faster rate of growth in productivity in manufacturing than in the service industries. It is concluded that difference in the supply characteristics of the two sectors is the main cause of the structural change. Both writers also suggest that constancy of product shares implies similar income elasticities of demand for the product of the two sectors. These conclusions, however, must be subject to two qualifications. First, the approach adopted does not allow for possible interaction between demand and supply.3 Demand and supply effects are assumed to be independent. But, as shown below, supply effects, as a result of differences in rates of productivity change, are likely to affect the relative rates of growth of product of the two sectors. Hence, constancy of product shares does not necessarily imply that demand factors are neutral. Interactive effects occur because different rates of productivity change, affect relative prices, which in turn lead to price substitution between the products of the two sectors.4 importance of these effects depends therefore on the differences in the rates of productivity change and the price elasticities of demand for the products of the sectors. following illustration shows how the effect operates.5 Let m equal the continuously compounded percentage rate of change in service sector employment over time minus the percentage rate of change in goods sector employment. Then as an approximation where r is the percentage rate m -r(nn,) + (rr,)(-1), of increase in real income, ns is the income elasticity of demand for services, nt0 is the income elasticity of demand for goods, rs is the percentage rate of increase in total factor proReceived for publication January 23, 1973. Revision accepted for publication January 30, 1974. * All the computer simulations required for this study were carried out by Margaret Wood. Helpful comments on an earlier draft were made by Dr. C. I. Higgins, Dr. R. G. Gregory, Mr. J. S. Marsden. Some of the data needed for this study are not available in official Australian statistics and were specially estimated. Notes on estimates are available from the author. complete set of equations used in the model, together with the usual tests of significance, are also available from the author. 1 In the first (1940) edition of The Conditions of Economic Progress Clark observed that studying economic progress in relation to the economic structure of different countries, we find a very firmly established generalization that a higher average level of real income per head is always associated with a high proportion of the working population engaged in tertiary industries . (pp. 6-7). Clark was not, of course, the first economist to discuss changes in industry structure; see, for example, Marshall (1938), pp. 276-277, and Clark himself drew attention to Petty's writings on this topic, in the 17th century (Clark (1957), pp. 176-177). But Clark's analysis is, however, more comprehensive than that of earlier writers. 2 For example, in Australia (Dowie (1970), p. 222) and in the United States (Fuchs (1957), pp. 6-8). Comparison of rates of increase in employment by sector for other countries is given in O.E.C.D. (1970). 3 This does not imply that Fuchs and Dowie are unaware of the importance of the interaction, but the results assume that they are insignificant. 4 cf. Baumol (1967) for a discussion of the relationship between changes in productivity, prices and demand. 5 This formulation was suggested by a referee.